2021
DOI: 10.1002/jmv.26931
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatic analysis of structural and epitope variations in the spike and Orf8 proteins of SARS‐CoV‐2/B.1.1.7

Abstract: A newly emerged strain of SARS-CoV-2 of B.1.1.7 lineage has caused a significant surge in the SARS-CoV-2 infections in the UK. In this study, changes in the epitopes of spike and orf8 proteins in SARS-CoV-2 of B.1.1.7 lineage were investigated. Genomic alignment of the SARS-CoV-2/B.1.1.7 with SARS-CoV-2/Wuhan showed the presence of several mutations in orf1a/b, spike, orf8, and N proteins of SARS-CoV-2/B.1.1.7. Molecular models of spike and orf8 proteins were constructed by homology modeling. Superimposition b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…The ORF8 gene encodes a rapidly evolving protein of SARS-CoV-2, and many variants of this protein have been reported ( Alkhansa et al, 2021 ; Fahmi et al, 2021 ; Hussain et al, 2021 ; Pereira, 2021 ; Zinzula, 2021 ). A recent X-ray crystallography study of ORF8 reported found that SARS-COV-2 ORF8 can form dimers or unique large-scale assemblies through Cys20 and 73YIDI76 motifs ( Flower et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ORF8 gene encodes a rapidly evolving protein of SARS-CoV-2, and many variants of this protein have been reported ( Alkhansa et al, 2021 ; Fahmi et al, 2021 ; Hussain et al, 2021 ; Pereira, 2021 ; Zinzula, 2021 ). A recent X-ray crystallography study of ORF8 reported found that SARS-COV-2 ORF8 can form dimers or unique large-scale assemblies through Cys20 and 73YIDI76 motifs ( Flower et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…SC-2 variant B.1.1.7 contains numerous synonymous and nonsynonymous mutations, of which the spike gene mutations 69-70del, N501Y, and P681H received most attention due to their potential effect on virus infectivity ( 12 , 13 ). For diagnostic purposes, however, the N501Y mutation is not variant-specific, as it was identified in several variants other than variant B.1.1.7, such as B.1.351 and the P.1 variant ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the capacity to distinguish between different lineages in a time scale of hours is currently possible only using qPCR. SC-2 variant B.1.1.7 contains numerous synonymous and non-synonymous mutations, of which the Spike gene mutations 69-70del, N501Y, and P681H received most attention due to their potential effect on virus infectivity (14)(15). For diagnostic purposes, however, the N501Y mutation is not variant-specific, as it was identified in several variants other than variant B.1.1.7, such as B.1.351 and the P.1 variant first discovered in Brazil (16).…”
Section: Discussionmentioning
confidence: 99%